SWOT ANALYSIS OF VEGETABLE AND PROCESSED VEGETABLE EXPORT - Vlahović, Branislav; Stevanović, Simo; Puškarić, Anton (Economics of Agriculture, 2008)
The basic aim of researches is to perceive demonstrated trends,structure and regional destination of export of vegetable and processed vegetable from the Republic of Serbia. Fresh and processed vegetable - frozen,dried (dehidrated) and canned vegetable are being analyzed in this paper. Authors gives suggestions that must increasse vegetable export. Export of vegetable and processed vegetable realized growth tendency. In export the most participation has fresh vegetable (26,2%), then frozen vegetable (25,2%), canned vegetable (23,1%) and dried vegetable (21,2%). Absence of marketing concept of economic entity, absence of national institution assistance and agrarian protectionism of developed countries are restrictive factor of export promotion from the Republic of Serbia.